DFT Calculations of 2,5-Diphenyl Furan against SARS-CoV-2 Mpro based on Molecular Docking Approach - Jeyavijayan, S.; Ramuthai, M.; Murugan, Palani (Asian Journal of Chemistry, 2022)
FTIR, FT-Raman and density functional theory (DFT) studies of 2,5-diphenyl furan (DPF) has been carried out to interpret the molecular structure, vibrational frequencies and its intensities. From the estimation, we obtained the HOMO-LUMO energy gap as 2.7113 eV, which is clearly significant the charge transfer occurs within the molecule. The intramolecular interaction and delocalization of the charges has been studied using NBO analysis. In addition, molecular electrostatic potential (MEP) calculations were also performed. The hydrogen bond interactions and binding energy of 2,5-diphenyl furan were estimated using molecular docking studies. The docking investigation was carried out to confirm the repressive nature of title molecule against SARS-CoV-2 main protease (Mpro) proteins.